Delivery Modality Affect Neonatal Levels of Inflammation, Stress, and Growth Factors - Kiilerich, Pia; Cortes, Rikke; Lausten-Thomsen, Ulrik; Borbye-Lorenzen, Nis; Holmgaard, Solveig; Skogstrand, Kristin (Frontiers in Pediatrics, 2021)
Introduction: As part of the study CODIBINE, Correlations and Diagnoses for Biomarkers in New-borns, the main objective of the study was to explore neonatal inflammation, stress, neurodevelopment and growth factors after in-labor and pre-labor caesarean section compared to vaginal delivery. Increasing evidence has shown that birth delivery mode has an impact on imminent and long-term child health. However, the effect of the timing of caesarean section is insufficiently elucidated. The main objective of the study was to explore the effect of different delivery modes, vaginal delivery compared to caesarean section with or without initiation of labor, on the infants. Methods: We designed a retrospective cohort study, including dried blood spot samples from mature (gestational age ≥37) new-borns delivered in the years 2009-2011. The new-borns were divided into three groups after delivery mode: 1) pre-labor caesarean section (n=714), i.e. caesarean delivery without initiation of labor, 2) in-labor caesarean section (n=655), i.e. caesarean section after initiation of labor, and 3) vaginal delivery (n=5897). We measured infant levels of inflammatory (IL-18, MCP-1, CRP, sTNF RI), stress- (HSP-70), growth- (EGF, VEGF-A), and neurotrophic factors (BDNF, NT-3, S100B) 2-4 days after birth. Results: The neonatal levels of inflammatory and stress-markers were significantly lower, while the levels of growth factors were higher after pre-labor caesarean section compared to vaginal delivery. The biomarker levels were similar after in-labor caesarean section and vaginal delivery. Removing cases with pre-labor rupture of membranes and artificial rupture of membranes in the calculations did not change the results. The levels of neurotrophic factors were unaffected by delivery form. Males had generally higher levels of inflammation and lower levels of growth and neurotrophic factors. Overall, the levels of inflammatory markers increased, and the growth factors decreased with increasing gestational age Conclusion: The biomarker levels indicates that the labor process has an important effect on the fetal immune system and level of stress, regardless if the delivery ends with caesarean section or vaginal birth.